SOME ISSUES OF JURIDICAL REGULATORY OF OIL AND GAS PRODUCTION FOR NATIONAL SECURITY AND DEFENCE NEEDS OF UKRAINE - Pasika, S.; Chomko, D.; Opanasenko, O.; Khomiakov, D.; Skyba, O.; Horbachuk, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This article presents an analysis of regulations, dealing with certain issues of oil and gas production for national security and defence needs of Ukraine. General trends of developing the petroleum sector, oil and gas production as a constituent of national security and defence of Ukraine were reviewed and analysed. The absence of a system in the legal regulation of oil and gas production industry to meet the needs of security and defence pose a real threat to the national security and defence of Ukraine, therefore this topic is highly relevant in present cricumstances. The issues of juridical regulatory of oil and gas production for national security and defence needs of Ukraine is becoming highly relevant in conditions of insufficient resource supply, reduction of stocks of hydrocarbon fuel, dependence on a monopoly supplies of energy resources and ineffective using of resources in security and defence sectors. In addition, a large number of indirect domestic factors, namely: the absence of clearly defined strategic goals, priorities and tasks of socio-economic, military-economic and scientific and technical development of Ukraine; high dependence of the national economy on foreign markets; insufficient level of protection of the infrastructure from terrorist attacks and sabotage; ineffective security management of the infrastructure and life support systems, etc. only reinforce the need for a speedy solution of this issue.